Enhancing the livelihoods of marginalized indigenous women through customary forests in Bali, Indonesia - Lukas R. Wibowo; Maharani Hapsari; Rini Astuti; Pantja Pramudya; Digby Race; Dewi Ratna Kurniasari; Ismatul Hakim (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2023)
This study examines how, why, and under what conditions marginalized women of customary communities can contribute and gain access to the benefits of the social forestry programme. We found that customary communities' dependence on forest resources creates a structure that divides labour and situates women within a particular set of socio-economic roles in the family and in the public economic spheres. These roles are subject to continuous negotiation of power as the customary community responds to the challenges brought by dynamic economic processes, demographic change, and the impacts of climate change. The communitarian-based local community, which asserts a rigid puritanism ideology, is able to maintain social identity, territory, and preservation of customary forests. On the downside, marginalized indigenous women who are involved in exogenous marriages are denied access to natural resources, local leadership, and residence rights. This is a part of a product of intersectional gendered relations that form the material bases of women's working lives and cultural roles as part of a broader customary community.
Keywords: Q23; R28; 330; marginalized women; puritanism; social forestry; communitarian